The X-ray variation of M81* resolved by Chandra and NuSTAR. Issue 2 (13th April 2023) - Niu, Shu; Xie, Fu-Guo; Wang, Q Daniel; Ji, Li; Yuan, Feng; Long, Min
ABSTRACT: Despite advances in our understanding of low-luminosity active galactic nuclei (LLAGNs), the fundamental details about the mechanisms of radiation and flare/outburst in hot accretion flow are still largely missing. We have systematically analysed the archival Chandra and NuSTAR X-ray data of the nearby LLAGN M81*, whose L bol ∼ 10 −5 L Edd . Through a detailed study of X-ray light curve and spectral properties, we find that the X-ray continuum emission of the power-law shape more likely originates from inverse Compton scattering within the hot accretion flow. In contrast to Sgr A*, flares are rare in M81*. Low-amplitude variation can only be observed in soft X-ray band (amplitude usually ≲2). Several simple models are tested, including sinusoidal-like and quasi-periodical. Based on a comparison of the dramatic differences of flare properties among Sgr A*, M31*, and M81*, we find that, when the differences in both the accretion rate and the black hole mass are considered, the flares in LLAGNs can be understood universally in a magnetohydrodynamical model.